2012
DOI: 10.1097/tp.0b013e318270f3c0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effector Function of CD4-Independent, CD8+ T Cells Is Mediated by TNF-α/TNFR

Abstract: Background Liver parenchymal cell allografts initiate both CD4-dependent and CD4-independent, CD8+ T cell-mediated acute rejection pathways. The magnitude of allospecific CD8+ T cell in vivo cytotoxic effector function is maximal when primed in the presence of CD4+ T cells. The current studies were conducted to determine if and how CD4+ T cells might influence cytotoxic effector mechanisms. Methods Mice were transplanted with allogeneic hepatocytes. In vivo cytotoxicity assays and various gene-deficient reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…These findings are consistent with the interpretation that alloprimed CD8 + T cells mediate cytotoxicity of alloprimed IgG1 + B cells through recognition of allopeptide presentation by MHC I. Since our prior studies demonstrate that the in vitro cytotoxicity assay preferentially reflects perforin-mediated cytotoxicity (17), we limit the interpretation of these results of allospecificity and MHC I/TCR cell-cell contact interactions to CD8 + T cell perforin-mediated cytotoxicity. In addition, we performed a similar side-by-side in vitro cytotoxicity assay for CD8 and B cell co-cultures using transwell membranes.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…These findings are consistent with the interpretation that alloprimed CD8 + T cells mediate cytotoxicity of alloprimed IgG1 + B cells through recognition of allopeptide presentation by MHC I. Since our prior studies demonstrate that the in vitro cytotoxicity assay preferentially reflects perforin-mediated cytotoxicity (17), we limit the interpretation of these results of allospecificity and MHC I/TCR cell-cell contact interactions to CD8 + T cell perforin-mediated cytotoxicity. In addition, we performed a similar side-by-side in vitro cytotoxicity assay for CD8 and B cell co-cultures using transwell membranes.…”
Section: Resultssupporting
confidence: 85%
“…Despite alloantibody downregulation following bulk CD8 + T cell adoptive transfer to CD8 KO recipient mice, transplant survival was no different in CD8 KO recipients with or without adoptive transfer (day 14 for both). This is not surprising since bulk CD8 + T cells also reject hepatocytes (17,2527). …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to acting as a ligand to TNFRs, TNFα elicits outside-to-inside signals (reverse signaling) (15). In the liver, TNFα/TNFR signaling has been linked to several biological processes, including liver regeneration (16), regulation of CD8 + T cell cytotoxicity (17), and mechanisms of fulminant hepatitis (18) and fibrogenesis (19). Based on our previous report that TNFα Biliary atresia is an obstructive cholangiopathy of infancy that progresses to end-stage cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that both B7-1 (CD80) and B7-2 (CD86) costimulatory molecules on DCs were required for IgG1 and IgG2a responses (31). TNF-α pathway was important for activating cytotoxic effector CD8 + T cells in the absence of CD4 T cells (32). This study provides evidence that a CD4 genetic defect led to developing other compensatory immune components even in a mock (PBS) treatment condition.…”
Section: Discussionmentioning
confidence: 99%